Eat pray love [videorecording (DVD)] - Murphy, Ryan, 1965-; Crudup, Billy, 1968-; Franco, James, 1978-; Bardem, Javier, 1969-; Roberts, Julia, 1967-; Davis, Viola, 1965-; Jenkins, Richard, 1947-; Gilbert, Elizabeth, 1969- (Sony Pictures Home Entertainment, 2010)
A happily married woman who is trying to get pregnant realizes that her life needs to go in a new direction. After a very painful divorce, she risks everything and embarks on a journey around the world that becomes a quest for self-discovery.